Meningkatkan Literasi Kesehatan Melalui Pojok Literasi Inklusif: Upaya Pencegahan Stunting Berbasis Teknologi di Pedesaan Kalimantan Selatan: Enhancing Health Literacy Through an Inclusive Literacy Corner: A Technology-Based Approach to Stunting Prevention in Rural South Kalimantan - Hendera, Hendera; Yunus, Muhammad; Fitriah, Aziza; Nadilla, Dhea; Dewi, Alya Puspita; Hidayah, Alfina; Rijal, Muhammad; Anggraini, Pitria; Hidayatullah, Rahmat; Susanti, Marisa; Putri, Annisa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The community service program "Sehat Mandiri Patih Muhur Baru: Towards a Prosperous Village Through Inclusive Literacy Corner" was implemented to improve community knowledge and understanding of nutrition, health, and stunting prevention in Patih Muhur Baru Village, Barito Kuala Regency, South Kalimantan. This program integrates digital technology and practical health tools in the Inclusive Literacy Corner as an easily accessible center for health information and monitoring. The implementation methods include socialization, training of health cadres, technology application, mentoring, and evaluation. Results show significant improvements in community knowledge and awareness about balanced nutrition, exclusive breastfeeding, stunting prevention, and independent health monitoring. The Inclusive Literacy Corner recorded an average of 2 visitors per day with a total of 60 visits in the first month. Surveys indicate an increased understanding of stunting (80%), exclusive breastfeeding practices (85%), and utilization of health services (90% for Posyandu). The main challenges include limited internet access and low levels of digital literacy. This program demonstrates the potential of an inclusive health literacy approach in improving rural community health and supporting stunting prevention efforts.